2016
DOI: 10.1007/978-3-319-49586-6_51
|View full text |Cite
|
Sign up to set email alerts
|

PUEPro: A Computational Pipeline for Prediction of Urine Excretory Proteins

Abstract: Abstract.A computational pipeline is developed to accurately predict urine excretory proteins and the possible origins of the proteins. The novel contributions of this study include: (i) a new method for predicting if a cellular protein is urine excretory based on unique features of proteins known to be urine excretory; and (ii) a novel method for identifying urinary proteins originating from the urinary system. By integrating these tools, our computational pipeline is capable of predicting the origin of a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Charge is a factor for determining which proteins can be filtered through the glomerular membrane. Wang et al found that transmembrane domains and the radius of gyration are also prominent features of urine excretory proteins [24]. Published studies have observed that proteins with a radius smaller than 1.8 nm can pass through the GBM-slit diaphragm barrier, whereas proteins with a radius larger than 4.0 nm are retained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charge is a factor for determining which proteins can be filtered through the glomerular membrane. Wang et al found that transmembrane domains and the radius of gyration are also prominent features of urine excretory proteins [24]. Published studies have observed that proteins with a radius smaller than 1.8 nm can pass through the GBM-slit diaphragm barrier, whereas proteins with a radius larger than 4.0 nm are retained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, developing a computational method for accurately predicting urine excretory proteins could solve these problems to a certain extent. However, there is very little research focused on building a computational model for predicting urine excretory proteins [3,24]. The existing methods can be carried out in two main steps: (1) selecting features from constructed feature sets; and (2) applying a machine learning algorithm for training by using the selected features.…”
Section: Introductionmentioning
confidence: 99%
“…Survival analysis analyzed the relationship between genes and patient survival, which was carried out through the platform R2 (R2: Genomics Analysis and Visualization Platform) [20]. The predictive analysis of urinary protein excretion was analyzed by website developed by Wang and Du [19].…”
Section: Gene List Analysismentioning
confidence: 99%
“…As described in the introduction, serum and urine tumor markers are important for tumor diagnosis, which prompts us to predict and analyze these genes. Table 2 shows the predicted results of urinary excretion of proteins carried out by the website developed, by Wang and Du [19]. The top seven differentially expressed genes in pancreatic cancer were analyzed to predict whether their protein products were urinary secretory proteins.…”
Section: Prediction Of Urinary Excretory Proteinmentioning
confidence: 99%
See 1 more Smart Citation